2020
DOI: 10.26582/k.52.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular resistance training on the performance of 5-km runners

Abstract: The study aimed to identify the effect of a neuromuscular resistance training protocol (NRTP) on the performance of 5-km distance runners. This study included 18 male runners (age=29.3±3.2 years, fat percentage=11.3±2.6%, body height=1.77±.04 m, body mass=73.4±4.4 kg, time in 5 km=20.6±2.4 min, training years=4.3±0.7 years). First, volunteers were anthropometrically evaluated, and they performed one-repetition maximum (1RM) 45º leg press (LP) strength test. Second, they performed an incremental protocol in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Ten studies [ 4 , 23 , 25 28 , 33 37 ] analyzed the outcome immediately after the intervention. Eleven [ 19 21 , 25 , 27 , 29 31 , 33 35 , 37 ] also analyzed outcomes 24 h later, whereas 9 [ 19 22 , 27 , 31 , 33 35 ] also included outcomes 48 h later. The funnel plot shows symmetrical results and high concentration at the top of the pyramid indicating low risk of bias of studies included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [ 4 , 23 , 25 28 , 33 37 ] analyzed the outcome immediately after the intervention. Eleven [ 19 21 , 25 , 27 , 29 31 , 33 35 , 37 ] also analyzed outcomes 24 h later, whereas 9 [ 19 22 , 27 , 31 , 33 35 ] also included outcomes 48 h later. The funnel plot shows symmetrical results and high concentration at the top of the pyramid indicating low risk of bias of studies included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The time to complete one kilometer was evaluated in two studies. Low [ 23 ] used a PAP protocol in which a significant reduction in time was observed, whereas in Guimarães [ 35 ] there was an increase in the time to complete 5 km when comparing the values pre vs post 30 min and post 48 h ( p = 0.02 and p = 0.04, respectively). As for the distance covered, Taipale [ 28 ] used combined training protocols and reported that there was no significant difference between control or experimental conditions (11.6 ± 0.9 / 11.7 ± 1.0 km).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations